2019
DOI: 10.1016/j.algal.2019.101415
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of lipid droplets in the diatom Phaeodactylum tricornutum

Abstract: Diatoms are a major phylum of phytoplankton biodiversity and a resource considered for biotechnological developments, as feedstock for biofuels and applications ranging from food, human health or green chemistry. They contain a secondary plastid limited by four membranes, the outermost one being connected with the endoplasmic reticulum (ER). Upon nitrogen stress, diatoms reallocate carbon to triacylglycerol storage inside lipid droplets (LDs). The comprehensive glycerolipid and sterol composition and the archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(137 citation statements)
references
References 147 publications
(178 reference statements)
12
124
0
Order By: Relevance
“…Various species of green algae sequester carotenoids in LDs, which may shield the photosynthetic apparatus from excessive light, reduce reactive oxygen species, serve as a sink for excess photosynthates or protect LD lipids from oxidation. Evidence of several pigments in P. tricornutum and F. solaris LDs has been found, including beta-carotene and fucoxanthin, as well as fucoxanthin-chlorophyll a/c binding proteins [37][38][39]. Our lab has made similar observations (unpublished) but the presence and function of carotenoids or other isoprenoids, in diatoms has not been explored in detail yet.…”
Section: The Corementioning
confidence: 72%
See 4 more Smart Citations
“…Various species of green algae sequester carotenoids in LDs, which may shield the photosynthetic apparatus from excessive light, reduce reactive oxygen species, serve as a sink for excess photosynthates or protect LD lipids from oxidation. Evidence of several pigments in P. tricornutum and F. solaris LDs has been found, including beta-carotene and fucoxanthin, as well as fucoxanthin-chlorophyll a/c binding proteins [37][38][39]. Our lab has made similar observations (unpublished) but the presence and function of carotenoids or other isoprenoids, in diatoms has not been explored in detail yet.…”
Section: The Corementioning
confidence: 72%
“…TAGs store large amounts of energy, carbon and membrane components, while simultaneously shielding the cell from the potential cytotoxicity of free fatty acids [34][35][36]. Thin-layer chromatography of LDs isolated from P. tricornutum confirms they are indeed composed mostly of TAG [37]; however recent lipidomic analysis has suggested that some sterols are present in lower abundance [38].…”
Section: The Corementioning
confidence: 97%
See 3 more Smart Citations